Pengaruh Investasi, Upah Minimum dan Inflasi Terhadap Pengangguran di Indonesia (Periode Tahun 2019-2023) - Farah Qalbia; Salma Arobani (Pusat Riset dan Inovasi Nasional, 2022)
The high population in Indonesia continues to increase, resulting in an increase in the number of existing workers. The current high number of workers exceeds the existing number of job opportunities. The supply of labor that is greater than the demand for labor will result in an increase in the number of unemployed. A large number of unemployed can result in various socio-economic problems in society such as crime and others. This research aims to find out the influence of Investment, Minimum Wage and Inflation on Unemployment in Indonesia. Using data for five years from 2019 to 2023. The data analysis technique used is secondary data processing using SPSS 25.